Opportunities and Challenges of Investment Activities: The Case of Selected Areas in Jimma Zone (Global Journal of Human-Social Science, 2017)
The purpose of this paper is to explicitly identify the major opportunities and challenges of investment activities in selected areas of Jimma zone Seka Waterfall Asendabo Hydro-Electric power Yebu Beekeeping and Jimma Museum in order to make the line open for further advanced research Furthermore indicating some of the investment opportunities for investors and providing possible solutions to the challenges observed were investigated Information has been gathered from both primary and secondary sources of data The pre-prepared written questionnaires and structured observation were primary one whereas document analysis belonged to secondary sources of data In addition to this structured interview was also employed for triangulation of research findings reality Simple random sampling method has been used for collection of data processing and analyzing was performed accordingly Jimma Zone has investment opportunities with a potential to accommodate various types of agro-industries that could make agricultural resources produced in the areas of its row material s production Some of the inputs for this sub-sector agro industry include cereals oil-seeds fruits vegetables coffee tea spices cotton honey animal and animal products milk and milk products processing enterprises such as tannery meat canning honey processing fruit and vegetable processing could be established in the zone particularly in the stated urban areas Lack of resources and political factors were the major factors contributing to the limited level of investment activity followed by social factors and lack of awareness Climatic condition of the areas and others such as corruption was some challenges which limit investment activity in the zone To overcome these and other problems that contribute to low investment activities in the zone developing infrastructure facilities matching the activities with the climate of the area conducting panel discussions as well as me
Keywords: Climatic condition advanced research investment opportunities